2009
DOI: 10.1002/cncr.24034
|View full text |Cite
|
Sign up to set email alerts
|

Survival of distinct Asian groups among colorectal cancer cases in California

Abstract: BACKGROUND It has been reported that Asian ethnicity confers a survival benefit in colorectal cancer (CRC) compared with other ethnicities, but it is not known if this is limited to specific Asian subsets. In the current study, the authors attempted to determine differences using data from the large, population-based California Cancer Registry (CCR). METHODS The authors conducted a case-only analysis of CCR data (1994–2003), including descriptive analysis of relevant clinical variables. Overall survival univ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 27 publications
1
14
0
Order By: Relevance
“…That is, relative to other groups, Asians have higher rates of distal colon cancer, which is associated with a decreased risk of mortality. This further confirms the findings of previous studies (Le et al , 2009). We also found that Indian/Pakistani patients had better DSS than did other groups even after adjusted by age, tumour stage, grade, and tumour site.…”
Section: Discussionsupporting
confidence: 93%
“…That is, relative to other groups, Asians have higher rates of distal colon cancer, which is associated with a decreased risk of mortality. This further confirms the findings of previous studies (Le et al , 2009). We also found that Indian/Pakistani patients had better DSS than did other groups even after adjusted by age, tumour stage, grade, and tumour site.…”
Section: Discussionsupporting
confidence: 93%
“…The persistent racial/ethnic survival differences, despite controlling for numerous variables, may be explained by differences in biology,33‐37 individual‐level SES,3 acculturation,38, 39 lifestyle,40 beliefs,41, 42 refusal of43, 44 and compliance with treatment,43, 44 post‐treatment surveillance,12, 13 and access to high‐quality cancer care,14 which were not investigated in the current study. Differences in tumor site distribution and genetics may explain the high survival rates observed among Asians.…”
Section: Discussionmentioning
confidence: 92%
“…Differences in tumor site distribution and genetics may explain the high survival rates observed among Asians. Relative to whites, Asians have higher rates of distal colon cancer, which is associated with a decreased risk of mortality 33. For blacks, poor survival may be caused by biologic features that contribute to aggressive tumor behavior7 or by inherited or acquired genetic abnormalities,35‐37 which may have an impact on response to therapy 37…”
Section: Discussionmentioning
confidence: 99%
“…Our findings are in agreement with several studies citing higher overall rates of survival in CC in Asians using state or county-level registries. 21,22 One of these studies also provided evidence that much of this survival benefit is due to genetic factors rather than socioeconomic factors. 21 Because our model accounts for socioeconomic c a b o e t a l h o s p i t a l t y p e a n d c o l o n c a n c e r d i s p a r i t i e s factors but not for genetic factors, there is the potential for inflation of perceived OS advantage in these patients.…”
Section: Overall Survival Outcomesmentioning
confidence: 99%